Perancangan Sistem Informasi Desa Pagergunung Berbasis Web dengan Framework Laravel - Krisdiantoro, Ahmad; Saian, Pratyaksa Ocsa Nugraha (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The village administrative center, or Village Government, is located in rural areas.Data management must be handled carefully and accurately to be beneficial in implementing government policies or programs. Information dissemination in the village is still not effective. The purpose of this research is to provide assistance to the village government in carrying out its duties and providing useful information to the community. The benefits that can be obtained through this research are that with the creation of this information system, the village government can get an overview of the benefits if the information system is made with its full functionality. The research method used is the Waterfall method, system design using Unified Modeling Language (UML), and user interface creation using Figma. The system application is built using the Laravel framework, Php, MySql database, and Visual Studio Code application.The population in this study is the Pagergunung Village Community with a sample of 30 people. The results of this study indicate that after conducting functional testing using the Black Box method, all functions run perfectly, achieving a success rate of 100%. User experience testing with three parameters shows that 87.66% of respondents agree that the application shows good performance, 85.99% of respondents agree that the application is easy to use, and 84.88% of respondents are satisfied with the application that has been built. It can be concluded that the creation of an information system using the Laravel framework can help and facilitate the tasks of village officials and provide useful information to the community.